Learning to read transforms phonological into phonographic representations - Chotiga Pattamadilok; Shuai Wang; Deirdre Bolger; Anne-Sophie Dubarry (Scientific Reports, 2025)
Abstract Learning to read changes the nature of speech representations. One possible change consists in transforming phonological representations into phonographic ones. However, evidence for such transformation remains surprisingly scarce. Here, we used a novel word learning paradigm to address this issue. During the learning phase, participants learned unknown words in both spoken and written forms. Following this phase, the impact of spelling knowledge on the auditory perception of the novel words was assessed at two time points through an unattended oddball paradigm, while the Mismatch Negativity component was measured by high density EEG. Immediately after the learning phase, no influence of spelling knowledge on the perception of the spoken input was found. Interestingly, one week later, this influence emerged, making similar sounding words with different spellings more distinct than similar sounding words that also shared the same spelling. Our finding provides novel neurophysiological evidence of an integration of phonological and orthographic representations that occurs once newly acquired knowledge has been consolidated. The resulting ‘phonographic’ representations may characterize how known words are stored in literates’ mental lexicon.